Real‐world use of pomalidomide and dexamethasone in double refractory multiple myeloma suggests benefit in renal impairment and adverse genetics: a multi‐centre UK experience. (17th February 2017) - Maciocia, Nicola; Melville, Andrew; Cheesman, Simon; Sharpley, Faye; Ramasamy, Karthik; Streetly, Matthew; Jenner, Matthew; Benjamin, Reuben; Schey, Steve; Maciocia, Paul; Popat, Rakesh; D'sa, Shirley; et al.
Summary: Myeloma patients who become refractory to immunomodulatory agents (IMiDs) and bortezomib have poor survival, with limited therapeutic options. Pomalidomide has shown improved survival and good tolerability in this patient cohort in clinical trials, but real world data are scarce. We retrospectively analysed all patients treated with pomalidomide at five UK centres between 2013 and 2016. Of 85 patients identified, 70 had sufficient information for response assessments. Median age was 66 years [40–89], 96·5% were refractory to IMiDs, 72·9% were refractory to both an IMiD and bortezomib and 92·9% were refractory to their last treatment. Of 45 patients with fluorescence in situ hybridization results 64% had adverse risk, 19 patients (22·4%) had an estimated glomerular filtration rate <45 ml/min. Grade ≥3 non‐haematological toxicities occurred in 42·4%, and grade ≥3 neutropenia and thrombocytopenia in 38% and 24% respectively, but only 18·8% had dose reductions. The overall response rate was 52·9%. At a median follow‐up of 13·2 months, median progression‐free survival was 5·2 months [95% confidence interval (CI) 4·150–6·238], and median overall survival was 13·7 months (95% CI 11·775–15·707). No significant difference was seen in response, survival or tolerability by renal function, age or cytogenetic risk. This real‐world data support the results seen in published clinical trials.